PENGARUH STRATEGI PROMOSI TERHADAP VOLUME PENJUALAN PADA MEUBEL RORRE - Yusuf Toban; Victor. R. Pattipeilohy (Jurnal Administrasi Terapan, 2023)
Determining the right promotion strategy is one form of the company's efforts to win the business competition. The current research aims to examine the effect of promotional strategies on the sales volume of new furniture products. This research is explanatory in nature through a survey method using a questionnaire instrument for data collection and is measured using a Likert scale. The sampling technique was purposive sampling, with a total sample of 100 respondents. Data analysis technique using multiple linear regression. The results showed that the promotion mix strategy, namely advertising, personal selling, sales promotion, and direct marketing, was partially able to increase sales volume of rorre furniture products. Keywords: Marketing Mix; Sales Volume;